Decrease in longitudinal strain in heart transplant recipients is associated with rejection - Podrouzkova, Helena; Bedanova, Helena; Tretina, Martin; Korinek, Josef; Stepanova, Radka; Hruskova, Jana; Nemec, Petr; Konecny, Tomas; Orban, Marek (Biomedical papers, 2015)
Background: Around 20-40% of heart transplant patients experience moderate to severe rejection within the first year after heart transplantation. Endomyocardial biopsy (EMB) is a gold standard for diagnosing heart transplant rejection. There is a need for non-invasive alternatives that allow for early, safe and reliable diagnosis of acute graft rejection prior to the onset of clinical symptoms.Aims: Our aim was to investigate the potential of speckle tracking derived strain analysis in the diagnosis of acute graft rejection.Methods: Patients indicated for EMB consented to a trans-thoracic echocardiography examination (TTE) within 2 hours of the EMB. Of this cohort, those with at least 2 EMBs separated ≥ 1 week, and whose TTE could be analyzed for strain, were included. The relationship between strain and EMB results was evaluated.Results: Of the 43 patients included (mean age 51.33±1.79, 67% male), 23 had findings of rejection identified on at least one EMB and at least one EMB without rejection for comparison. A significant deterioration in the longitudinal strain during rejection compared to non-rejection was found on apical 4-chamber views (-11.51±0.91 vs -13.48±0.96, P=0.025) and apical 2-chamber views (-11.84±0.78 vs -14.43±0.83, P=0.002). In the patients in whom no rejection was identified on either EBM, there was no significant change in longitudinal strain values at two different time points.Conclusion: Worsening of longitudinal strain was associated with acute cellular rejection. Routine TTE-based strain analysis could help in early detection of cardiac rejection and timing of EMB.
Keywords: echocardiography; heart transplantation; graft rejection